The effects of rural development non-governmental organisations governance on societal transformation in Elandsdoorn Moutse, Limpopo Province - Makofane, Happines Refilwe (My University, 2022)
This study provides a theoretical foundation for researchers to investigate the effects of rural development non-governmental organisations’ governance on societal transformation. The research also assessed the mission statements from a non-profit organisation perspective, considering their operational activities in trying to address NGOs’ governance. Although, historically, these statements have been used almost exclusively in a management context. The nine components of a mission statement provide direction for the researcher to examine statements and practitioners to create and modify the statements. This study marries the rural development non governmental organisations’ governance and societal transformation literature. Creating a fruitful new area for marketing research and practice. The recommendations will hopefully give guide and recommend tools for aligning NGOs operational activities with their mission statements to promote good governance practice. The study investigated the effects of rural development non-governmental organisations’ governance on societal transformation. The aim was to investigate the types of rural development actions and role players in Elansdoorn Moutse, to analyse the governance of the actions of rural development role players, to examine the scales and profiles of NGOs acting in rural development, to delineate the effects of rural development NGOs’ governance on societal transformation, and to propose measures for improved governance of actions and enhancement of societal transformation credential of rural development NGOs in developing countries. The study found that if rural development NGOs were well governed, they would have the power and potential to transform the society.
Thesis (M.Dev. (Planning and Management)) -- University of Limpopo, 2022
Keywords: Rural Development; Non-Governmental; Organisations; Governance; Societal Transformation; Rural development -- South Africa -- Limpopo; Non-governmental organizations -- South Africa; Social change; Corporate governance -- South Africa